Systematic review of organisation‐wide, trauma‐informed care models in out‐of‐home care (OoHC) settings. (23rd July 2018) - Bailey, Cate; Klas, Anna; Cox, Rachael; Bergmeier, Heidi; Avery, Julie; Skouteris, Helen
Abstract: Trauma in early childhood has been shown to adversely affect children's social, emotional, and physical development. Children living in out‐of‐home care (OoHC) have better outcomes when care providers are present for children, physically, psychologically, and emotionally. Unfortunately, the high turnover of out‐of‐home carers, due to vicarious trauma (frequently resulting in burnout and exhaustion) can result in a child's trauma being re‐enacted during their placement in OoHC. Organisation‐wide therapeutic care models (encompassing the whole organisation, from the CEO to all workers including administration staff) that are trauma‐informed have been developed to respond to the complex issues of abuse and neglect experienced by children who have been placed in OoHC. These models incorporate a range of therapeutic techniques, and provide an overarching approach and common language that is employed across all levels of the organisation. The aim of this study was to investigate the current empirical evidence for organisation‐wide, trauma‐informed therapeutic care models in OoHC. A systematic review searching leading databases was conducted for evidence of organisation‐wide, trauma‐informed, out‐of‐home care studies, between 2002 and 2017. Seven articles were identified covering three organisational models. Three of the articles assessed the Attachment Regulation and Competency framework (ARC), one study assessed the Children and Residential Experiences programme (CARE), and three studies assessed The Sanctuary Model. Risk of bias was high in six of the seven studies. Only limited information was provided on the effectiveness of the models identified through this systematic review, although the evidence did suggest that trauma‐informed care models may have significantly positive outcomes for children in OoHC. Future research should focus on evaluating components of trauma‐informed care models and assessing the efficacy of the various organisational care models currently available.